Self-cross-linking kinetics of unsaturated polyester poly(fumaric-co-itaconic-co-butanediol). (June 2015) - Shao, Fenjuan; Yang, Qun; Li, Lanying; Lu, Danian
Unsaturated polyester poly(fumaric-co-itaconic-co-butanediol) (poly(FA-co-IA-co-BD)) was prepared with fumaric acid (FA), itaconic acid (IA), and 1, 4-butanediol (BD) by melt polycondensation, and its self-cross-linking kinetics was investigated through the percentage of insoluble gel fraction ( Q s ) and conversion degree of C=C (DC). The results showed that poly(FA-co-IA-co-BD) had the highest Q s and DC, when the mole ratio of FA and IA was 1:0.96, which meant that the polyester had the maximum extent of self-cross-linking. And the polyester had the maximum rate constant ( k ) and the smallest activation energy ( E a ). The value of k was temperature dependent, and the higher the temperature, the higher the value of k . Thermodynamics parameters such asΔ ≠ G m ϴ, Δ ≠ H m ϴ, a n d Δ ≠ S m ϴ were also discussed. The results showed that, Δ ≠ G m ϴ > 0, the self-cross-linking reaction of the poly(FA-co-IA-co-BD) occurred at high temperature. The self-cross-linking reaction was an exothermic reaction, Δ ≠ H m ϴ was equivalent to E a .Δ ≠ S m ϴ < 0, the product in the transition state was more ordered. When the mole ratio of FA to IA was 1:0.96, poly(FA-co- IA-co-BD) was the most ordered in the transition state and had the smallestΔ ≠ S m ϴ, and the C=C in the polyester self-cross-linked easily.